The Impact of Land Reclamation Project on Fisherman of Tanjung Tokong - Chia Huey, Tung; Seow, Ta Wee; Kai Chen, Goh; Shafii, Haryati (Research in Management of Technology and Business, 2021)
Land reclamation as a development from a construction site has greatly become a part of people's attention around the world. This study explored the survey land reclamation project in Penang. As we know that the problem of land reclamation is affecting the soil structure destroy, had affected the pollution of sea area. However, during the construction process did not implemented well mitigation, resulting in damage to the soil structure, affecting the surrounding marine biota. Therefore, this study attempts to explore the effect cause by reclamation activities to fishermen and determine the action taken by the contractor to mitigate for damage caused by reclamation at Tanjung Tokong. The research was conducted in Tanjung Tokong, Penang. Quantitative and quantitative approach adopted for this research. Data collection was made by obtained effect cause by reclamation activities to fishermen through questionnaire with 40 respondents. The data was analyzed by using SPSS. For the qualitative method which through interview session and online method carry out with 3 contractors from CCCC company. The results about of the effect cause by reclamation activities to fishermen had impact to income of fisherman is majority agree with 80% and with the highest mean 4.35. Besides that, during the operation of reclamation, effectively follow up the proper planning and establishment method of reclamation will prevent the major environmental problem. As conclusion, the research objectives were achieved and implement the rock protection is importance to soil stabilization and coastal protection. This is important to mitigate the damage from the reclamation.